2018
DOI: 10.1002/joc.5881
|View full text |Cite
|
Sign up to set email alerts
|

Does the modern‐era retrospective analysis for research and applications‐2 aerosol reanalysis introduce an improvement in the simulation of surface solar radiation over China?

Abstract: Surface incident solar radiation (Rs) is a key parameter of energy and water cycles of the Earth. Reanalyses represent important sources of information on Rs. However, reanalyses Rs may have important bias due to their imperfect parameterizations and input errors of cloud and aerosol. NASA's Global Modelling and Assimilation Office has recently released Version 2 of the Modern‐Era Retrospective Analysis for Research and Applications (MERRA2), which incorporates a reanalysis of atmospheric optical depth for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that climate models have difficulty simulating low‐level clouds, and corresponding cloud radiation effects. For example, Feng and Wang (, ) pointed out that both MERRA‐2 and MERRA had a high mean bias of 43.86 and 38.63 W m −2 over China due to the underestimations of cloud cover. Existing studies have also indicated that aerosols might be a possible reason of the great uncertainties (larger positive biases) for reanalyses in China (Xia et al ., ; Jia et al ., ; You et al ., ; Feng and Wang, , ), where heavy pollution is occurring due to rapid development of economy and population explosion.…”
Section: Results and Analysismentioning
confidence: 99%
“…Previous studies have shown that climate models have difficulty simulating low‐level clouds, and corresponding cloud radiation effects. For example, Feng and Wang (, ) pointed out that both MERRA‐2 and MERRA had a high mean bias of 43.86 and 38.63 W m −2 over China due to the underestimations of cloud cover. Existing studies have also indicated that aerosols might be a possible reason of the great uncertainties (larger positive biases) for reanalyses in China (Xia et al ., ; Jia et al ., ; You et al ., ; Feng and Wang, , ), where heavy pollution is occurring due to rapid development of economy and population explosion.…”
Section: Results and Analysismentioning
confidence: 99%
“…Existing studies (Feng & Wang, ; Ma et al, ; Wang et al, ) also show that the CERES EBAF surface product provides reliable estimations of monthly R s . Feng and Wang () find that CERES EBAF has a bias of 7.94 W/m 2 compared with observation and 7.53 W/m 2 compared with SunDu‐derived R s from 2000 to 2014. The comparison results of CERES EBAF, GEWES‐SRB, and ISCCP‐FD‐SRF from Li, Xin, and Peng () show that CERES EBAF have lowest root‐mean‐square error (RMSE, 14.73 W/m 2 ) compare with solar radiation measurements in China.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, R s measurements are sparsely distributed in China. In spite of uncertainty in short time scales, SunDu‐derived R s data have their advantage in quantifying annual to decadal variability of R s (Feng & Wang, ; Wang, ).…”
Section: Methodsmentioning
confidence: 99%
“…Merging multisource data can be a practical way to improve Rs data with accurate long-term variations [51][52][53][54][55][56]. The large number of SunDu observations (~2400 stations) with large spatial coverage ( Figure 1 Our previous studies have shown reanalyses have substantial biases due to imperfect parameterization of cloud and aerosols [26,51,58]. Considering the advantages of SunDuderived R s and reliable cloud distribution from satellite retrievals, we recently combined ground-based sunshine duration with satellite cloud and aerosol data to produce high resolution long-term R s [59].…”
Section: Introductionmentioning
confidence: 99%